Experiential marketing : consumer behaviour, customer experience and the 7Es - Batat, Wided, 1981- (Routledge, Taylor & Francis Group, 2019)
Why do some brands make us feel good, while others frustrate us? What makes us engage with certain brands, rebuy the same products, return to the same store or revisit the same destination over and over again? Is there a framework underlying how past and lived shopping experiences can affect our future experiences, our buying decisions, and our brand loyalty? In this exciting new book, Wided Batat introduces readers to the new customer experience framework and the era of the "Experiential Marketing Mix." She introduces the concept of the 7Es (Experience, Exchange, Extension, Emphasis, Empathy, Emotional touchpoints, Emic/Etic process); a tool that focuses on the consumer as a starting point in marketing strategies. By using these, companies can design suitable, emotional, and profitable customer experiences in a phygital context (physical place and digital space) including both offline and online digital experiences. Batat argues that a traditional product-centric should be replaced by the appropriate mix of 7Es, based upon a more consumer/experience-centric logic. Experiential Marketing is a guide to building experiences consumers cannot forget. It will be of interest for CEOs, brand managers, marketing and communication professionals, students, and anyone eager to learn more about how to design the ultimate customer experience in a new phygital. In this book, Professor Batat combines theory and practice and gives readers an overview of: the origins and the rise of the customer experience logic, the 7Es of the new experiential marketing mix, and the challenges for the future.